PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT LARAS PRIMA SAKTI SELUMA - Eli Suryani; Melda Yunita (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2022)
This study aims to see the effect of leadership style and work discipline on the performance of employees of PT Laras Prima Sakti Seluma. This research is a survey research, with quantitative data analysis with a sample of 32 employees using total sampling technique. The data technique uses observation and interviews. The data analysis technique used instrument test, classical assumption test, multiple linear regression, determinant coefficient (R2) and hypothesis testing. The results of this study can be seen from the multiple linear regression test using SPSS Y = 6.338 + 0.295 X1 + 0.207 X2. From the results of hypothesis testing, there is a significant influence of leadership style (X1) and work discipline (X2) on the performance of PT. Laras Prima Sakti Seluma. Hypothesis testing with the F test obtained Fcount of 19.148 > F table (3.3277) with a p value (sig.) of 0.000 <0.05, which means it can be concluded that H3 is accepted, meaning that the variables of leadership style and work discipline are jointly (simultaneously) affect employee performance. Keywords: Leadership Style, Work Discipline and Employee Performance